Beginning Microsoft SQL Server 2012 programming - Atkinson, Paul (John Wiley & Sons, 2012)
Get up to speed on the extensive changes to the newest release of Microsoft SQL Server The 2012 release of Microsoft SQL Server changes how you develop applications for SQL Server